Factors Influencing Decision Quality: An Empirical Study on Managers in Public Institutions in Jordan (Global Journal of Management and Business Research, 2019)
The aim of this study was to explore factors influencing decision quality made in public institutions in Jordan. On the basis of the literature, four factors were determined as factors associated to decision quality; moral intensity, information quality, group cohesiveness and decision experience. Each factor along with decision quality was assessed using six indicators adopted from previous studies. A questionnaire was developed and utilized in this study to collect data. The population of the study comprised managers, assistant managers and authorized employees to participate in decision making in 15 public institutions in Irbid governorate in Jordan. The total number of population was 210 participants, all of them included in the study. A total of 210questionnaires were distributed to the participants and 179 were returned complete with a response rate of 85.23%. Using SPSS and Amos to analyze the data, the results accepted the hypotheses that moral intensity, information quality, group cohesiveness and decision experience were significantly and positively have an influence on decision quality.
Keywords: moral intensity; information quality; group cohesiveness; decision experience; decision quality; public institutions; jordan